Blue light modulates the interactive effects of far-red light and day–night temperature difference on the growth, morphology and physiology of arugula and lettuce - Ali, Awais; Jeong, Sang Jun; Zhen, Shuyang; Cocetta, Giacomo; Masabni, Joseph; Niu, Genhua (Frontiers in Plant Science, 2025)
IntroductionFar-red (FR; 700–800 nm) light and the difference between day and night temperature (DIF) interactively regulate plant morphology and growth. FR light and +DIF synergistically promote stem elongation, often reducing leaf expansion and overall growth. In contrast, blue light effectively suppresses stem elongation. We hypothesized that when stem elongation is suppressed by blue light, the combination of FR light and +DIF may enhance leaf expansion, instead of stem elongation, thereby enhancing photon capture and final biomass.MethodsTo determine the interactive effects among FR light, DIF, and blue light, arugula ‘Astro’ and romaine lettuce ‘Green Forest’ were grown under two blue light photon flux densities [50 (low B) and 120 (high B) μmol m−2 s−1] x three FR fractions (0.01, 0.17, and 0.33) x three DIF treatments [+8 DIF (28/20 °C), 0 DIF (24/24°C), -8 DIF (20/28°C)]. Total photon flux density was 200 μmol m−2 s−1 for the low and 270 μmol m−2 s−1 for the high blue treatments.ResultsOur results showed that FR light and +DIF interactively regulated leaf expansion and stem elongation, but this effect was diminished at high blue light. In both species, under low blue light, FR light and +DIF synergistically promoted stem elongation. However, high blue light effectively suppressed the excessive stem elongation induced by FR light and +DIF, preserving their positive effects on total leaf area and biomass. In arugula, FR light and +DIF synergistically enhanced leaf expansion, rather than stem elongation, under high blue light. Morphological acclimation, such as thinner leaves under FR light and +DIF, led to a decrease in single-leaf daily carbon gain, whereas high blue light improved daily carbon gain by enhancing leaf thickness and pigment levels. Furthermore, while FR light generally reduced phenolic content and antioxidant capacity, +DIF and blue light increased flavonoid and phenolic levels as well as antioxidant capacity.DiscussionOverall, these results demonstrate that blue light is a critical determinant of whether the individual and interactive effects of FR light and +DIF are beneficial or detrimental to crop growth.